2015
DOI: 10.1097/bot.0000000000000257
|View full text |Cite
|
Sign up to set email alerts
|

Can Geriatric Hip Fractures be Managed Effectively Within a Level 1 Trauma Center?

Abstract: Therapeutic level III. See Instructions for authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The utility and success of such services is well-documented in the literature. 11 - 14 After implementation of an orthopedic-hospitalist comanagement service for patients who were traditionally admitted to the general medicine service, Bracey et al cites a reduction in length of stay by 1.6 days without an increase in 30-day readmission or mortality. This is consistent with the study by Phy et al who noted a reduction in length of stay from 10.6 to 8.4 days and a reduction in time to surgery from 38 to 25 hours under a similar coordination initiaitive.…”
Section: Discussionmentioning
confidence: 99%
“…The utility and success of such services is well-documented in the literature. 11 - 14 After implementation of an orthopedic-hospitalist comanagement service for patients who were traditionally admitted to the general medicine service, Bracey et al cites a reduction in length of stay by 1.6 days without an increase in 30-day readmission or mortality. This is consistent with the study by Phy et al who noted a reduction in length of stay from 10.6 to 8.4 days and a reduction in time to surgery from 38 to 25 hours under a similar coordination initiaitive.…”
Section: Discussionmentioning
confidence: 99%
“…Dedicated clinical pathway use has also been shown to lower the odds of four common complications of hospitalisation after hip fracture: deep vein thrombosis, pressure ulcers, surgical site infection and urinary tract infection . Multidisciplinary models of orthogeriatric care can improve outcomes and decrease inpatient complications following hip fracture, particularly for the elderly . Integrating the orthogeriatrician into the care plan for hip fracture patients provides an opportunity to identify and reduce risk factors pertinent to these frail patients at risk of delirium and other common geriatric complications, while monitoring for poly‐pharmacy and drug interactions that may occur during pain management in the acute peri‐operative period.…”
Section: Methodsmentioning
confidence: 99%
“…Coordination is described as the means to deliver a plan of care to patients following hip fracture that involves the organization of medical and multidisciplinary teams to the deliver best practice care (Coventry et al., 2017; Holte et al., 2015). Nine studies reported coordination as a feature of the APN role (Collinge et al., 2013; Coventry et al., 2017; Doshi et al., 2014; Holte et al., 2015; Lau et al., 2013; Lin et al., 2009; Ling et al., 2015; Lynch et al., 2015; Pickles et al., 2014) (Table 3; Table S1). Coordination was a key function and involved: case management; organization of medical teams for perioperative optimization; management of the hip fracture clinical pathway; and implementation of essential resources and services post discharge.…”
Section: Resultsmentioning
confidence: 99%